Effectiveness of an online application of the health action process approach (HAPA) theory on oral hygiene intervention in young adults with fixed orthodontic appliances: a randomized controlled trial - Weizi Wu; Lulu Hu; Yihan Chen; Feiran Cao; Sixie Ding; Tingting Wu; Jianguang Xu (BMC, 2022)
Abstract Background This randomized controlled trial aimed to evaluate the effectiveness of an online application based on HAPA theory on oral hygiene promotion in young adults with fixed orthodontic appliances. Methods A WeChat mini-program (called "Clean Teeth") based on HAPA theory was designed beforehand to improve oral-health behaviors and oral hygiene, and 44 participants aged 17-29 with fixed orthodontic appliances were recruited. Participants of the experimental group (n = 22) received the "Clean Teeth" mini-program, in addition to care as usual, and the control group (n = 22) only received routine oral health education. Data were collected during three orthodontic check-ups: baseline (T0), 6 weeks of follow-up (T1), and 12 weeks of follow-up (T2). All participants completed questionnaires assessing oral health behaviors and the psychosocial factors of the HAPA model and accepted the clinical examinations involving the dental plaque index and the gingival bleeding index. Results After a 12-week intervention, the plaque index and gingival bleeding index in the experimental group were significantly lower than that in the control group. The psycho-social parameters of social effects, expected outcomes, and action control were improved significantly after treatment, among which social effects increased significantly only in the experimental group but not in the control group. Conclusions The HAPA theory-based mini-program had positive effects on oral-health behavior promotion and oral hygiene among young adults with fixed orthodontic appliances. Trial registration This study was retrospectively registered in the Chinese Clinical Trial Registry, with the number CTR2200056731, dated 12/02/2022. http://www.chictr.org.cn/index.aspx .